The implementation of authentic activities for learning: a case study - Baccarini, David (Murdoch University, 2004)
The situated cognition theory of learning advocates that students should engage in the same types of activities in which expert practitioners in the various disciplines engage. Situated cognition promotes the use of authentic activities for learning and understanding. This paper reports the findings of a case study for implementing and evaluating authentic activities for learning in an undergraduate construction degree program. A key finding is that authentic activities should be introduced early and developed and applied progressively throughout the program in order to maximise effective learning outcomes. Students appreciated the value of learning through authentic activities, particularly the integration of different disciplines and areas of knowledge. However, students initially struggled with the ambiguity of problems to be solved and the range of possible acceptable solutions.